Salidroside Alleviates Diabetic Cognitive Dysfunction Via B3galt2/F3/Contactin Signaling Pathway in Mice. (21st February 2023) - Lv, Pan; Zuo, Zhongfu; Liu, Wenqiang; Zhao, Lipan; Wang, Yufei; Wang, Xiaobai; Yu, Shengxue; Yu, Hongdan; Zhang, Tianyi; Bi, Jing; Liu, Xuezheng
Graphical abstract: Highlights: β-1, 3-galactosyltransferase 2 (B3galt2) contributes to diabetic encephalopathy. F3/contactin is involved in B3galt2-mediated hippocampus neuron apoptosis. Diabetic cognitive dysfunction can be alleviated by salidroside. B3galt2/F3/Contactin pathway plays a vital role in diabetic cognitive dysfunction. Abstract: Diabetes is frequently accompanied by cognitive impairment with insidious onset, and progressive cognitive and behavioral changes. β-1, 3-galactosyltransferase 2 (B3galt2) contributes to glycosylation, showing a clue for neuronal apoptosis, proliferation and differentiation. However, the role of B3galt2 in diabetic cognitive dysfunction (DCD) has not been investigated. In the present study, we aimed to explore the role of B3galt2 in DCD. Additionally, the potential therapeutic effects of salidroside on DCD was also explored. Diabetic C57BL/6J mice showed cognitive dysfunction together with down-regulated B3galt2. Overexpression of B3galt2 reversed the cognitive decline of diabetic C57BL/6J. Moreover, cognitive impairment was aggravated in B3galt2 +/− diabetic mice compared with C57BL/6J diabetic mice. Immunohistochemistry fluorescence indicated that B3galt2 and F3/Contactin were co-localized in the hippocampal regions. Importantly, the expression of F3/Contactin can be regulated by the manipulation of B3galt2, overexpression of which assuaged hippocampal neuronal damage, protected the synapsin, and reduced neuronal apoptosis in diabetic mice. Interestingly, SAL alleviated DCD and reversed the expression of B3galt2 in diabetic C57BL/6J mice. These findings indicate that inhibition of B3galt2/F3/Contactin pathway contributes to DCD, and participates in SAL reversed DCD.